Studi Tentang Kegiatan Pengembangan Koleksi (Collection Development) pada Perpustakaan Perguruan Tinggi di Wilayah Priangan Timur Provinsi Jawa Barat - Yunus Winoto; Sukaesih Sukaesih (Program Studi Ilmu Perpustakaan UIN Alauddin, 2016)
This study aims to determine the activities of collection development at the college library in the eastern Priangan West Java Province. The location of this research conducted in UPT. Siliwangi Library (UNSIL) Tasikmalaya and UPT. Galuh University Library (Unigal) Ciamis. The focus of this study include six (6) aspects, aspects of the needs analysis, policy-making collection development, selection activities, procurement of library materials, weeding activities and evaluation activities. The method used is descriptive method with case study. For data collecting technique is done through interviews, observation and literature study. Based on the survey results revealed that UPT. Library UNSIL Tasikmalaya and UPT. Library Unigal Ciamis in general has done the stages in development such as requirements analysis, policy making the selection, the selection, procurement of library materials, as well as to evaluate, but the implementation is not optimal. As for weeding stages UPT library materials. Library UNSIL Tasikmalaya and UPT. Library Unigal Ciamis has not carried out due to face many obstacles between the limited collection of owned and issue procedures and the limited human resources (HR) is available.